Prospect, challenges and minimizing the risk of implementing a manufacturing plants in Bangladesh economic zone - Uddin, Mohammad Farhad (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2024.